Demokrasi Patronase Dan Praktik Politik Uang : Pengalaman Pilkada Sumut Oleh Mahasiswa PPKN Unimed - Jekson Saragih; Putri Widia Ningsih; Muthiah Latifah; Esra Julita Br PA; Julia Ivana (Universitas 17 Agustus 1945 Semarang, 2024)
Indonesia, with its dynamic democratic process, is often characterized by patronage politics and money politics during the Regional Head General Election (PILKADA). This phenomenon has become an integral part of the political reality of this country. Patronage politics, which involves the use of power or position to influence political support, and political practices involving money that financially benefit interest groups, have a significant impact on the democratic process. This research aims to understand how democratic patronage and money political practices are carried out by candidates candidates based on regional election experience by UNIMED PPkn students. There are several strategies to overcome this problem, and implementing these strategies must involve cooperation between the government, supervisory institutions, civil society and the media in order to create a cleaner and more transparent political environment.